2004
DOI: 10.1002/j.2333-8504.2004.tb01938.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Item Characteristics That Are Related to the Difficulty of Toefl Dialogue Items

Abstract: The purpose of this study is to explore the relationship between a set of item characteristics and the difficulty of TOEFL ® dialogue items. Identifying characteristics that are related to item difficulty has the potential to improve the efficiency of the item-writing process The study employed 365 TOEFL dialogue items, which were coded on 49 variables, including 5 significant variables reported in Nissan, DeVincenzi, and Tang (1996). Of the 5 significant variables in Nissan et al., 3 correlated significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(65 citation statements)
references
References 20 publications
6
56
1
2
Order By: Relevance
“…When L2 listeners are lower proficiency, they may be overwhelmed in trying to process even shorter passages, especially as the "shorter" passages examined by Carrell et al were quite long compared to those examined in earlier studies (~2.5 minutes compared to 10 words in Henning [1990], and < 20 seconds in Kostin [2004] and Nissan et al [1996]). …”
Section: Consensus In the Literaturementioning
confidence: 84%
See 4 more Smart Citations
“…When L2 listeners are lower proficiency, they may be overwhelmed in trying to process even shorter passages, especially as the "shorter" passages examined by Carrell et al were quite long compared to those examined in earlier studies (~2.5 minutes compared to 10 words in Henning [1990], and < 20 seconds in Kostin [2004] and Nissan et al [1996]). …”
Section: Consensus In the Literaturementioning
confidence: 84%
“…However, Thompson and Rubin found that passage length interacted with other qualities of the passage: longer dramatic segments were better tolerated than longer news reports, suggesting that number of speakers, structure of the passage, or topic may interact with length. Nissan, DeVincenzi, and Tang (1996) found no effect of overall passage length in seconds on listening comprehension item difficulty, and Kostin (2004) found no significant effect of the total number of words in the passage on comprehension difficulty. However, the passages examined in both these studies were fairly short (< 20 seconds in length).…”
Section: Length Of Passagementioning
confidence: 92%
See 3 more Smart Citations